Strategic Governance of School Libraries: Bridging Infrastructure Limitations and Increasing Reading Motivation - Adam Pangestu; Khoirun Nisa'; Ida Faridah (Al-Qalam Institue, 2026)
This study aims to analyze the management of school libraries in increasing students’ reading enthusiasm through the stages of planning, implementation, and evaluation. The research employs a qualitative method with a descriptive approach to examine how library governance is carried out in supporting students’ literacy development. The findings indicate that effective library management includes systematic program planning, the implementation of library services and collection management, and continuous evaluation of library activities to encourage students’ reading interest. Although challenges remain, particularly related to infrastructure and supporting facilities, the strategies implemented have contributed to increasing students’ visits to the library and gradually fostering a stronger reading culture. The study implies that planned and sustainable library management plays a crucial role in enhancing students’ reading enthusiasm, and therefore requires consistent institutional support to strengthen literacy facilities, expand library collections, and develop innovative literacy programs.